Perlindungan Hukum Pemegang Hak Atas Tanah dalam Program Pendaftaran Tanah Sistematis Lengkap (PTSL) dalam Perspektif Kepastian Hukum - Ulupalu, Rauf (Jurnal HUKUM BISNIS, 2025)
The Complete Systematic Land Registration Program (PTSL) is a government initiative to accelerate land certification in Indonesia to ensure legal certainty and protection for landowners. However, the implementation of this program has raised various legal challenges, especially related to the protection of land rights holders from overlapping claims, administrative errors, and post-certification disputes. This study uses a normative legal method supported by empirical data to examine the extent of legal protection provided to landowners and evaluate the effectiveness of the PTSL program in realizing legal certainty. The results of the study indicate that although certification coverage has increased, data inconsistencies, weak coordination between institutions, and minimal public legal awareness reduce the effectiveness of legal protection. This article recommends strengthening institutional synergy, increasing data accuracy, and increasing legal education for the public to support justice and legal certainty for land rights holders. Keywords: PTSL, Land Certification, Landowner, Legal Certainty